MATHEMATICAL QUESTIONING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Xiangjie Zhang; Hailun Fu (STAI Hubbulwathan Duri, 2020)
This study aims to investigate students' mathematical questioning ability in junior high school students. The new phase of curriculum reform in China requires cultivating students 'innovative enthusiasm and practical abilities to some extent, the development of students' innovative abilities, which are prominently manifested in student inquiry learning. One of which is students' ability to ask questions. This research uses quantitative methods. Data collection was carried out using a questionnaire. A questionnaire to 80 junior high school students studied mathematics, and the reasons for the learning questions were analyzed. Data were taken in 2018 and 2019. Describe the motivation and resilience of junior high school students' math questioning abilities. They are trying to find ways to effectively improve junior high school students' math questioning skills. This study indicates that the frequency of asking students is still low, students still believe that the teacher is always right and never deny that the teacher teaches what is wrong. In further research, further research can be carried out on how to increase the frequency of student questions in teaching and learning activities